AN ANALYSIS OF RACIAL DISCRIMINATION IN ‘’MAX HAVELAAR’’ MOVIE - Kale, Kristina; Sulistyo, Teguh; Purnawati, Maria (Universitas Al-Qolam Malang, 2024)
The aim of the study is to find out the types of racial discrimination in the film Max Havelaar and to find out the causes of racial discrimination in the film Max Havelaar. The study used a descriptive qualitative design. Descriptive qualitative design is used to describe and explain what has been interpreted from the research object. The researchers conducted the research by watching the film